A case of scrofuloderma complicated with genital elephantiasis and saxophone penis. Issue 1 (January 2017) - Afsar, Fatma Sule; Seremet, Sila; Afsar, Ilhan; Karakuzu, Ali; Ermete, Murat
Abstract : Scrofuloderma is a type of secondary tuberculosis from an endogenous source, and it occurs by contagious spread from tuberculous lymph nodes, bones, or joints. Genital elephantiasis is a common sequela of filariasis and lymphomagranuloma venereum, and rarely does it follow tuberculosis. We report a case of a 29-year-old male patient diagnosed as scrofuloderma with genital elephantiasis and saxophone penis.